An ethnobotical study of medicinal plants used by Bajau community along Sulaman Bay in Tuaran, Sabah / Mayrlidzatul Farhain Misrah - Misrah, Mayrlidzatul Farhain (2016)
This study involved Penimbawan, Sambah, Bunga and Serusup that located along Sulaman Bay in Tuaran, Sabah, inhabited by the Bajau community. The objectives of this study are to identify species of medicinal plants and method of preparation used by Bajau community along Sulaman Bay in Tuaran, to classify in taxonomical, to construct a dichotomous key and to classify species of medicinal plants based on disease found along Sulaman Bay in Tuaran. Methodologies involved were pilot study, interview, plant collection, plant pressing, plant drying, plant mounting, plant classification, and dichotomous key. Five informants that have been interviewed, there are 57 species of medicinal plants were collected and recorded. The major preparation method used is boiled, followed by pounded then soaked. The total of 57 medicinal plants collected was belonging to 16 families which the most prominent are Euphorbiaceae, Rutaceae, Poaceae. A dichotomous key of medicinal plants also was constructed. A total of 28 diseases can be treated by using these medicinal plants which then categorized into 13 types of disease It is recommended in future to conduct more research on therapeutic value contain in medicinal plants to ensure and conserve the precious knowledge that plants have so future generations can keep the benefits for long time.